Efficacy of physiotherapy interventions late after stroke: a meta-analysis. Issue 2 (8th September 2010) - Ferrarello, Francesco; Baccini, Marco; Rinaldi, Lucio Antonio; Cavallini, Maria Chiara; Mossello, Enrico; Masotti, Giulio; Marchionni, Niccolò; Di Bari, Mauro
Abstract : Objective: Physiotherapy is usually provided only in the first few months after stroke, while its effectiveness and appropriateness in the chronic phase are uncertain. The authors conducted a systematic review and meta-analysis of randomised clinical trials (RCT) to evaluate the efficacy of physiotherapy interventions on motor and functional outcomes late after stroke. Methods: The authors searched published studies where participants were randomised to an active physiotherapy intervention, compared with placebo or no intervention, at least 6 months after stroke. The outcome was a change in mobility and activities of daily living (ADL) independence. The quality of the trials was evaluated using the PEDro scale. Findings were summarised across studies as effect size (ES) or, whenever possible, weighted mean difference (WMD) with 95% CI in random effects models. Results: Fifteen RCT were included, enrolling 700 participants with follow-up data. The meta-analysis of primary outcomes from the original studies showed a significant effect of the intervention (ES 0.29, 95% CI 0.14 to 0.45). The efficacy of the intervention was particularly evident when short- and long-distance walking were considered as separate outcomes, with WMD of 0.05 m/s (95% CI 0.008 to 0.088) and 20 m (95% CI 3.6 to 36.0), respectively. Also, ADL improvement was greater, though non-significantly, in the intervention group. No significant heterogeneity was found. Interpretation: A variety of physiotherapy interventions improve functional outcomes, even when applied late after stroke. These findings challenge the concept of a plateau in functional recovery of patients who had experienced stroke and should be valued in planning community rehabilitation services.